2002
DOI: 10.1002/hep.1840360621
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic manifestations of hepatitis C among United States male veterans

Abstract: Hepatitis C virus (HCV) has been associated with several extrahepatic conditions. To date, most studies assessing these associations involved small numbers of patients and lacked a control group. Using the computerized databases of the Department of Veterans Affairs, we carried out a hospital-based case-control study that examined all cases of HCV-infected patients hospitalized during 1992 to 1999 (n = 34,204) and randomly chosen control subjects without HCV (n = 136,816) matched with cases on the year of admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(114 citation statements)
references
References 47 publications
4
106
2
Order By: Relevance
“…26 Over the last decade, epidemiological data have demonstrated a possible link between porphyria cutanea tarda, lichen planus, Sjögren's syndrome and HCV. 27 More recently, HCV has been associated with fatigue 28 and insulin resistance though this association is weak. 29,30 HCV has also been implicated in the pathogenesis of acquired aplastic anemia, although this hematological disorder is uncommon in HCV infected individuals and the available evidence to support a causal relationship is very limited.…”
Section: Lymphoproliferative Disordersmentioning
confidence: 99%
“…26 Over the last decade, epidemiological data have demonstrated a possible link between porphyria cutanea tarda, lichen planus, Sjögren's syndrome and HCV. 27 More recently, HCV has been associated with fatigue 28 and insulin resistance though this association is weak. 29,30 HCV has also been implicated in the pathogenesis of acquired aplastic anemia, although this hematological disorder is uncommon in HCV infected individuals and the available evidence to support a causal relationship is very limited.…”
Section: Lymphoproliferative Disordersmentioning
confidence: 99%
“…[13][14] The major pitfall in the interpretation of both results was the small size of samples. More recently, one prospective cohort study in Northern California 15 and two case-control studies, one in the USA 16 and one in Italy, 17 tried to address the question in large cohorts of patients. The first found that HCV infection did not precede at significant rates the development of B-cell lymphoproliferative disorders, while the two others did show a significant association between HCV and lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that half a million cases occur worldwide annually, making primary liver cancer the fifth most common malignancy in men and the ninth in women [1][2][3][4][5][6]. Hepatocellular carcinoma (HCC) accounts for 85% to 90% of primary liver cancers [7] and the age-adjusted HCC mortality rate has increased in recent decades in Japan [8].…”
Section: Introductionmentioning
confidence: 99%